EFFECTS OF BLUE NPK FERTILIZER AND/OR BIOCHAR ON THE GROWTH AND YIELD OF OKRA (Abelmoschus esculentus L.) PLANT USING SILABUKAN SOIL - Sauti, Mohamad Suhaizrezal; Azman, Elisa Azura; Ismail, Roslan; Phooi, Chooi Lin; Lakulassa, Safikah (Jurnal Penelitian Pertanian Terapan, 2024)
A study was conducted in nethouse at the Sustainable Agriculture Faculty at University Malaysia Sabah, Sandakan campus, to study the effect of using blue NPK fertilizers (12:12:17) with a different biochar rate (0, 1 and 2 tonnes ha-1). The objective of this study was to determine the optimum rate of NPK blue and/or biochar fertilizer on the growth and yield of okra plant using Silabukan soil and to determine the nutrient content found in the soil before and after the study. There are 15 treatments that have been used in this study and have 3 replicates for each treatment. The design used is a completely randomized design (CRD). Data were analyzed using ANOVA one way. The results for vegetative growth showed that the treatment of N5B3 (400 kg ha-1 and 3 tonnes ha-1) had the highest tree height of 185.7 cm and the highest number of leaves of 31 sheets. For the results of yield, the N4B3 (300 kg-1 blue NPK and 3 tonnes ha-1 of biochar) treatment showed the highest yield of 7 pieces of fruit and 22 cm long. For the results of soil analysis, N1B1 (0 kg-1 blue NPK and 0 tonnes ha-1 biochar) treatment showed the highest pH reading of 6.3. N2B1 treatment (100 kg ha-1 and 0 tonnes ha-1) shows the highest alumunium conversion readings of 1.5 cmolc kg-1. N4B1 treatment (300 kg-1 blue NPK and 0 tonnes ha-1 biochar) showed the highest availability of phosphorus 0.0592 mg kg-1. In conclusion, the N4B3 treatment (300 kg-1 blue NPK and 3 tonnes of ha-1 biochar) showed the best growth to produce a large amount of okra fruit about 7 pieces per plant.